Вплив пасткових станiв на кiнетику люмiнесценцiї та наведеного поглинання свiтла наночастинками Si в SiO2 матрицi при збудженнi фемтосекундними лазерними iмпульсами - Kadan, V. M.; Indutnyi, I. Z.; Dan’ko, V. A.; Shepelyavyi, P. E.; Dmitruk, I. M.; Korenyuk, P. I.; Blonsky, I. V. (Publishing house "Academperiodika", 2018)
We report on the results of our researches dealing with nonlinearities caused by trap states in the lux-intensity characteristics of the intrinsic emission band of Si nanoparticles embedded into a SiO2 matrix and the dependence of the temporal characteristics of induced absorption on the pump femtosecond pulse fluence.